PEMANFAATAN DATA HASIL DIAGNOSTIK SISWA ASESMEN KOMPETENSI MADRASAH INDONESIA UNTUK PENGEMBANGAN KURIKULUM DI KOTA SAMARINDA - Hasanah, Arini; Natavia, Dini; Warman, Warman; Mulawarman, Mike Gede; Haryaka, Usfandi (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2024)
This study aims to analyze the utilization of diagnostic data from the Indonesian Madrasah Competency Assessment (AKMI) in curriculum development in Samarinda City. Amid the challenges of globalization and the need to prepare a high-quality young generation, responsive and adaptive education management has become increasingly crucial. AKMI, as a comprehensive assessment evaluating students' competencies in reading literacy, numeracy, science, and socio-cultural aspects, provides highly valuable data for improving education quality. This research adopts a mixed-methods approach, combining quantitative data from AKMI diagnostics conducted between 2021 and 2024 with qualitative data gathered through interviews and observations with stakeholders in Samarinda City. The findings indicate that AKMI data can be used to identify students' strengths and weaknesses across various competencies, which can then serve as the foundation for designing more adaptive and evidence-based curricula. As a recommendation, curriculum development strategies in Samarinda City should focus on improving numeracy and science literacy, while strengthening the already solid achievements in reading and socio-cultural literacy. This study is expected to provide guidance for developing curricula that are more responsive to students' needs and enhance the quality of learning in madrasah.